Detection of a Mixed-Strain Infection with Drug- and Multidrug-Resistant Mycobacterium avium Subspecies hominissuis in a Dog with Generalized Lymphadenomegaly - Cinzia Marianelli; Angelo Leonori; Romana Stecco; Carlo Giannantoni (Antibiotics, 2025)
Background Members of the Mycobacterium avium complex (MAC) have been documented to cause severe and disseminated infections in dogs, although such cases are sporadically reported. In this study, a comprehensive account of a rare case of generalised lymphadenomegaly caused by a mixed-strain infection with drug- and multidrug-resistant Mycobacterium avium subspecies hominissuis (Mah) in a Maremma sheepdog is presented. Methods Laboratory investigations, as well as the monitoring of the clinical signs displayed by the animal, were conducted throughout the course of a two-year drug therapy (based on rifampicin, azithromycin, and ciprofloxacin) and a two-year post-treatment follow-up period, until the death of the dog. Laboratory examinations included both solid and broth cultures from fine-needle aspiration samples of lymph nodes, molecular typing by 8-locus MIRUVNTR analysis and SNPs typing of five genetic regions (gyrB, rpsA, 3′hsp65, ITS and rpoB), and drug susceptibility testing towards seven antimycobacterial drugs. Results The results indicated the presence of two distinct genotypes of Mah, which exhibited different phenotypic characteristics, such as different drug susceptibility profiles and growth abilities in broth and solid media, suggesting a mixed-strain infection. Resistances to ethambutol alone, to ethambutol and clarithromycin, and to ethambutol, clarithromycin, rifampicin, and doxycycline were detected over the study. Conclusions Although the Mah strains isolated during the course of therapy showed sensitivity to the regiment, the complete eradication of the infection was never achieved. It has been hypothesised that the presence of drug-resistant and multidrug-resistant Mah strains in the animal may have been established at the onset of the infection or soon thereafter. The exposure to therapy has been suggested as a potential factor that could have favoured the growth of resistant strains, thereby rendering the therapy ineffective. The implications that the distinct phenotypic and genotypic ...